Kodowanie wartości prawnych w przepisach Konstytucji Rzeczypospolitej Polskiej z 1997 roku. Perspektywa aksjologicznej wykładni prawa - Kordela, Marzena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The derivative theory of interpretation of law assumes the rationality of the lawmaker according to which the lawmaker is guided in their work by a coherent, hierarchical and relatively stable system of values comprising three categories: legally binding, reference values and universal values. In order to adequately reconstruct the legally binding category, the directives of the axiological interpretation are used. Thus, each word and phrase of every text of a normative act, including the Polish Constitution, can be assigned a function of the carrier of legal values provided that they meet the conditions imposed on them by the appropriate interpretation directives.